Cultural Distance and Payment Method in French Cross-Border Acquisitions - Nguyen, Pascal; Belaounia, Samia (Management international / International Management / Gestiòn Internacional, 2020)
We study the role of cultural distance in the choice of payment method in cross-border acquisitions. Our results based on French acquirers show that cultural distance increases the likelihood of payment in cash, which is not the case of geographical distance and linguistic difference. We also find that the most significant dimension of culture is uncertainty avoidance and that cultural distance matters most when integration of the target into the acquirer’s organizational structure is expected to be challenging. These results suggest that cash payment is a means to achieve greater control over the target, particularly when the risk of dissent is high.